Experience of internationally qualified nurses providing palliative care in a New Zealand aged residential care facility. (2nd December 2021) - Angus, Elizabeth; Reid, Kate; Yamit, Sigred; Coe, Gill; Ryan, Bridget; Crichton, Sharyn
Abstract : Background: New Zealand is reliant upon internationally qualified nurses (IQNs) working within aged residential care (ARC), despite the fact that many of these nurses have limited or no ARC or palliative care experience before arriving in the country. Aims: To understand the issues faced by IQNs providing palliative care to people in ARC. To understand how the palliative aged residential care (PARC) specialist nurse team can best support IQNs. Methods: A thematic analysis was undertaken from five focus group interviews with IQNs (n=24) from ARC facilities in the Christchurch and Canterbury regions. Findings: Unfamiliarity with New Zealand 's palliative care and ARC systems, cultural differences and communication barriers caused internal struggles. Transitioning to a New Zealand approach to palliative care highlighted participants' adaptability and resilience. Consistent approaches to training and support by the PARC team and additional cultural training within New Zealand Competence Assessment Programmes (CAP) are required. Conclusion: Ongoing education, support and role modelling to develop confidence and reduce internal struggles are required for IQNs providing palliative care in ARC.